THE ROLE OF REGIONAL-SCALE FAULTS IN CONTROLLING A TRAPDOOR CALDERA, COROMANDEL PENINSULA, NEW ZEALAND - Smith N.; Cassidy J.; Locke C.A.; Mauk J.L.; Christie A.B. (My University, 2006)
Regional gravity data from an eroded Miocene to Pliocene volcanic arc exposed in the Coromandel Peninsula, New Zealand, delineate a circular -26-mGal, 15-km-diameter gravity anomaly. This anomaly, which has steep gradients on its northern and western margins but shallow gradients elsewhere, correlates with relatively young volcanic and volcaniclastic rocks within a broad topographic depression. Gravity modelling, using an exponentially decreasing density contrast with depth profile, requires very low-density rocks (ca. 2280 kg m-3) in the near-surface to account for the observed anomaly, giving a total depth of ca. 2.8 km for these rocks. The northern and western margins of this body dip steeply inward at 70°, whereas the southern and eastern margins have shallow inward dips (20-30°). The western margin coincides with the regional-scale Mangakino Fault, but the northern margin, recognizable only in the geophysical data (and named here the Ohinemuri Fault), is partially buried under younger volcanic rocks. We interpret these deep and steeply bounded, low-density volcanics in terms of a trapdoor caldera, faulted on its northern and western margins, with its hinge on the southern and eastern margins. Epithermal deposits are spatially associated with the Mangakino and Ohinemuri Faults, suggesting that both structures may have influenced hydrothermal fluid flow. These deposits pre-date caldera fill, indicating that caldera development followed pre-existing regional faults. These results delineate the subsurface geometry of a trapdoor caldera and highlight the role of pre-existing, regional-scale faults in controlling such caldera location and collapse. © 2005 Elsevier B.V. All rights reserved.
Keywords: COROMANDEL; DENSITY; GRAVITY MODEL; TRAPDOOR CALDERA; VOLCANISM; WAIHI; Pliocene; Miocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен